‘Wicked’ Philosophy – Philosophy of Science for Interdisciplinary Studies into Complex Problems - Tromp, Coyan (Philosophy and Realistic Reflection, 2025)
To confront complex, ‘wicked’ problems such as climate change and migration, science is essential. But what type of knowledge can science provide and what do we actually need? What is the role of the philosophy of science in clarifying what knowledge is required and how to bring it together? To address these pivotal questions, this article reviews three scientific approaches: the empirical cycle (the logical empiricist model reigning in the natural sciences), the hermeneutic cycle (the interpretive model mainly used in the social sciences and humanities), and the model cycle (a more recently emerging approach). Each has its strengths and limitations in dealing with complex problems. We discuss opportunities to combine the various approaches to gain the most from them and provide illustrative examples of how students can be encouraged to understand and integrate the different perspectives they contain. To enhance this, we propose a ‘wicked’ philosophy of science that takes complexity thinking as an overarching framework; as it enables us to combine realist and constructionist perspectives, it offers a more nuanced approach to knowledge acquisition. Given the post-truth society we live in, the proposed ‘wicked’ philosophy also advocates a broader rationality concept that includes emotive and value-laden aspects, and a reflexive science that continually assesses its impacts. The ultimate aim is to equip students with critical, reflexive, and integrative thinking skills that help prepare them for interdisciplinary research on complex problems, thus cultivating a scientific approach that contributes to finding solutions to the pressing challenges we are currently facing.